1,000-m Rowing Ergometer Time Trial Performance in Female and Male Collegiate Rowers - Oliwer Huzarski; Waldemar Pluta; Anna Lubkowska (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2022)
Introduction. The purpose of this study was to evaluate the time of covering a distance of 1000 m on a rowing ergometer by competitors of the Academic Sports Association of the Pomeranian Medical University and to relate the achieved results to the best results from the Polish Rowing Ergometer Academic Championships. Methods. 28 rowers were tested in the 1000 m "maximum" test (1000TM/t). In addition, correlations were sought between the time and power values obtained in the 1000 TM/t with the values of selected anthropometric indices (height and weight, body mass index BMI), hand grip strength, heart rate and body composition components (free fat mass FFM, skeletal muscle mass SMM). Results. The significant correlation between the time and power output in 1000TM/t and values of FFM, SMM, handgrip strength test as well as resting HR have been observed. Conclusion. The results obtained at 1000TM/t can be considered promising for the further training stage due to the fact that the study was conducted on a rowing ergometer under training conditions prior to a special training mesocycle shaping strength and speed, while the athletes competing at the event to which our results were related were in peak competitive performance.